Motivating Factors for Entrepreneurship and Development Divergences Across Arunachal Pradesh - An Analysis - Kumar, Amit (Journal of Global Economy, Business and Finance, 2025)
Entrepreneurship in Arunachal Pradesh, India, is influenced by a range of motivating factors and exhibits diverse development trajectories. Geographical remoteness, ethnic diversity, and limited infrastructure have contributed to unique entrepreneurial challenges and disparities. Cultural preservation, self - reliance, and job creation drive entrepreneurship among indigenous communities. Economic growth, improved livelihoods, and reduced dependency on agriculture motivate entrepreneurship in urban areas. Development disparities arise due to geographical variations, with regions closer to urban centres witnessing faster growth compared to more remote areas. Access to markets, education, and technology further contribute to divergences. Government policies and initiatives play a crucial role; proactive policies aimed at fostering entrepreneurship, like skill development programs and financial incentives, can narrow development gaps. The present study aims to analyze the motivating factors behind entrepreneurship in Arunachal Pradesh, India by explores resulting development disparities, stemming from geographical remoteness, infrastructure limitations, and varying access to resources.